Extração e caracterização cinético de lipase ácida presente na semente de mamona - Alves, Ediane de Sá (Universidade Federal de São Carlos, 2019)
Several studies have been conducted regarding acidic lipase from castor bean seed, most of them using the enzyme in the form of solid seed extract (SSE), which is extracted through grinding and removal of the oil. Kinetic studies of the oil hydrolysis catalyzed by SSE have already been done, but the estimated parameters are apparent, since it is a heterogeneous system where the substrates are found in different liquid phases while the enzyme is found in solid phase. In this context, enzyme extraction would eliminate possible diffusive effects from the use of SSE. The objective of this research was to find the best conditions for extracting the enzyme from the seed in order to perform the kinect study of the soluble enzyme. Once obtained, the soluble enzyme was used in the soybean oil catalysis under different conditions. The reaction speed depends on the interfacial area formed by oil drops and water. Thus, a study of the influence of stirring conditions in the hydrolysis initial speed. The results shows that in a reactional system, using 50 mL of reactional volume and a 3-bladed impeller, the initial hydrolysis velocity increases with the stirring rotation up to 1000 rpm, keeping constant for higher rotation speeds. These conditions were used to perform the kinetic study. The maximum activity for free enzyme was verified at the temperature of 37-40 ° C. After choosing an adequate enzyme concentration (linear region of the curve Vi=f(Ce)), the influence of substrate (oil) in the hydrolysis initial speed was studied, at pH of 4,5 and temperature of 37° C. A Michaelis-Menten model with substrate inhibition has been used to study the same reaction catalyzed by SSE and had good fitting to the experimental data Vi=f(Cs). The estimated intrinsic kinetic parameters were VMáx/Uhid(30,7x10-4±0,88x10-4 mmol.Uhid-1.min-1), Km (49,264 ± 2,37 mM) e Ks (866,80 ± 108,79 mM). When comparing these values and those obtained using enzyme in the SSE form, the values of VMáx/Uhid were higher and the value of Km was smaller for the soluble enzyme, indicating the presence of diffusional effects when SSE is used. Accordingly, the parameter Ks did not change, as it represents the influence of the oil drops coalescence for high oil concentrations, implicating on a decrease of substrate concentration, represented in the model as a kinetic substrate inhibition. This phenomenon was similar using either soluble or SSE enzyme.
Extraction and kinetic characterization of acid lipase present in castor bean seed
Keywords: Enzimas; Lipase; Cinética enzimática; Mamona; Enzymes; Enzyme Kinetics; Castor beans; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA